Transradial Approach to Cardiovascular Interventions: An Update - Sachdeva, Shilpa; Saha, Sibu (International Journal of Angiology, 2014)
Background Since the first cardiac catheterization in 1929, the procedure has continually evolved with advances in understanding, capabilities, and ease of operation. Though historically performed by cut down of the brachial artery, cardiologists soon learned that transfemoral access was both easier to perform and more efficacious with regard to patient outcome. In the last 20 years, the transradial approach has been adopted, and is being utilized with increasing frequency.Methods We conducted a survey of literature published concerning safety, efficacy, cost-effectiveness, and global uptake of transradial catheterization with specific attention to how transradial interventions compare with transfemoral interventions.Results This review of literature indicates that when performed by an experienced interventionalist, radial catheterization is as effective as femoral catheterization and has additional benefits of shorter length of hospital stay and reduced patient costs. Transradial access is superior to transfemoral access in some, but not all, clinical scenarios; in addition, it is an effective alternative for catheterization in patients contraindicated for transfemoral procedures. Adoption of radial access in the United States is at a faster rate than previously expected, though rate of use varies drastically worldwide.Conclusion The transradial approach is an excellent option for carrying out cardiovascular interventions, and will be adopted by more cardiologists in the upcoming years.
Keywords: radial artery; arterial access; vascular complications; cost-benefit analysis; worldwide adoption; feasibility studies